Peran United Nations Children’s Fund (UNICEF) dalam Program Humanitarian Actions Children sebagai Implementasi Hak Anak terhadap Anak-anak Palestina Tahun 2021 - Wardania, Rista Vauza; Utomo, Ario Bimo (Global and Policy Journal of International Relations, 2022)
Every child around the world has the right to obtain their rights which have been stated in theConvention on the Rights of the Child in 1989. The Convention on the Rights of the Child in 1989categorizes the age limit for children as all human beings under 18 years old. Every country isobliged to provide children's rights to all children without exception. In addition, InternationalOrganizations also play as a role in helping to provide children's rights as stated in the Conventionon the Rights of the Child (1989). UNICEF is one of an international organization under the auspicesof the United Nations, created to help children around the world to get their rights. One of UNICEF'sprograms in implementing children's rights is the Humanitarian Action for Children program whichwas formed in 2011 to help vulnerable children, such as victims of natural disasters, conflict victims,refugees, and victims of disease outbreaks, in obtaining their rights. This study describes the roleplayed by UNICEF through the Humanitarian Action for Children program in implementingchildren's rights for Palestinian children in 2021.Keywords: UNICEF, Children’s Rights, Palestinian Children, Humanitarian Actionsfor Children.DOI: https://doi.org/10.33005/jgp.v10i01.3575